2012
DOI: 10.1061/(asce)st.1943-541x.0000499
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Shear Behavior of Reinforced Concrete Pile Caps

Abstract: The application of bending theory based methods and strut-and-tie models for the design of pile caps to resist shear is still a subject of debate, with the latest Eurocodes permitting both methods but not giving much guidance as to their use. The former UK design standards for concrete buildings and bridges, recently withdrawn, gave more guidance and it is likely that these methods will continue to be used by designers.However, there is considerable discrepancy between these standards, particularly with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors developed a semi-empirical ST model (Bloodworth et al 2012;Cao 2009), verified against tests at UoS for caps over certain ranges of the geometric ratios n and μ (Table 1), which are respectively the LD and TD pile spacings (lx, ly) divided by pile diameter (hp). An empirically derived 90% of the LD reinforcement Ast was taken as the yielding tie, independent of μ.…”
Section: Fig 1 Dimensions Of a Typical Bridge Rc Four-pile Cap Undementioning
confidence: 99%
“…The authors developed a semi-empirical ST model (Bloodworth et al 2012;Cao 2009), verified against tests at UoS for caps over certain ranges of the geometric ratios n and μ (Table 1), which are respectively the LD and TD pile spacings (lx, ly) divided by pile diameter (hp). An empirically derived 90% of the LD reinforcement Ast was taken as the yielding tie, independent of μ.…”
Section: Fig 1 Dimensions Of a Typical Bridge Rc Four-pile Cap Undementioning
confidence: 99%
“…Notwithstanding, distributed reinforcement should be located along the bottom side of pile caps to control soffit crack width, which is a recommendation in most standards despite the contribution made to the strength design being ignored. In this regard, Bloodworth [21] after analyzing the failure of four-pile caps under full width load, proposed a modification factor on the STM to take this secondary reinforcement into consideration. Table 1 summarizes the reinforcement distribution by distinguishing: the main bunched reinforcement (A sB ), horizontal secondary reinforcement (A sH ) and vertical secondary reinforcement (A sV ).…”
Section: Pile Cap Reinforcement Arrangement By the Stmmentioning
confidence: 99%
“…The validation of the proposed model was investigated using 110 RC footing test results and other strut-and-tie models, and the results showed that the proposed model could give better accuracy and consistency. Other previous studies related to the strut-and-tie model can be found in the references (e.g., Adebar and Zhou 1996;Park et al 2008;Bloodworth et al 2012). In addtion, Jensen and Hoang (2012) proposed an upper bound plasticity approach for the strength prediction of reinforced concrete footings, and this approach can be considered a seismic loading Yong Yang et al Solids and Structures, 2020, 17(2), e257 3/16 complement to the lower bound strut-and-tie model.…”
Section: Introductionmentioning
confidence: 99%